Sistema de respostas de Bacillus sp. à toxicidade induzida pelo herbicida Callisto e princípio ativo - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2015)
Excessive use of herbicides for weed control in agriculture causes a selective pressure on soil microbiota and waters near application area, changing environmental balance. Some microorganisms have developed metabolic pathways for degradation of these xenobiotics, although tolerance and degradation processes can generate free radicals and affect survival. This study aimed to analyze the system of responses from soil and water strains, submitted to selective pressure by the herbicide Callisto®. Strains CCT7729 and CCT7730, isolated from soil and water, respectively, were identified as Bacillus sp., and showed different degradation routes, with different metabolites, already described in the literature. Mesotrione and its metabolites, and especially its commercial product Callisto, affected cell viability and altered cell membrane lipids from the tested strains, however, Bacillus sp. CCT7729 presented a more efficient system of responses to oxidative stress. This strain exhibited a greater efficiency to degrade mesotrione, lower rates of peroxide, lower rates of MDA, SOD high activity and low activity of catalase, when compared to Bacillus sp. CCT7730. Changes in membrane lipids can be considered as a defense against oxidative stress strategy. These results indicated the existence from a variety of metabolic pathways for mesotrione degradation to Bacillus sp. Probably metabolites induce different levels of toxicity in bacteria, and Bacillus sp. CCT7730 possibly degraded mesotrione in even harmful compounds, unlike the water line. It is possible that these different responses are related to the home environments of each strain, suggesting plasticity responses of Bacillus sp. for adaptation to toxic substances in different environmental contexts.
Keywords: catalase; degradação; estresse oxidativo; peroxidação lipídica; peróxido de hidrogênio; rotas metabólicas; superóxido dismutase; catalase; degradation; oxidative stress; lipid peroxidation; hydrogen peroxide; metabolic pathways; superoxide dismutase; CNPQ::CIENCIAS BIOLOGICAS::BIOQUIMICA::BIOLOGIA MOLECULAR